Double dome osteotomy for the treatment of cubitus varus in children - Eamsobhana, Perajit (Springer-Verlag, 2013)
PURPOSE: The purpose of this study was to report double dome osteotomy used to correct paediatric cubitus varus and to avoid lateral prominence after correction. METHODS: Eighteen children with cubitus varus underwent double dome osteotomy. Preoperative templating created from radiographs was used to determine the bone cuts. Double dome osteotomy created a proximal and distal cut, then varus deformity and sagittal alignment were corrected. The osteotomies were fixed with K-wires and immobilised in a long-arm cast. Radiographics and clinical histories were evaluated. Ulno-humeral angle pre and postoperative, range of motion and lateral prominent index were evaluated. RESULTS: The osteotomy was performed in 18 patients, with an average age of 7.5 years. All patients ended up with flexion of 130° or greater with full and symmetrical pronation and supination. The average ulno-humeral angle difference compared to the uninjured side was 3.27°. The mean of the lateral prominent index was −0.91. The mean follow up was 50.3 months (30–115 months). All of the patients had excellent clinical and radiographic alignment. No revisions were made in this series. One transient radial nerve palsy and one superficial infection occurred. CONCLUSION: This series demonstrates that double dome osteotomy can provide reliable correction of varus deformity and prevent lateral prominence with a minimal complication rate.